Tall or taller, pretty or prettier: Is discrimination absolute or relative? - Daniel S. Hamermesh (IZA Journal of Labor Economics, 2012)
Using microeconomic data sets from the United States and the Netherlands, this study considers how agents perceive characteristics that are discriminated against. It uses the examples of beauty and height to examine whether: 1) Absolute or relative differences in a characteristic affect labor-market and other outcomes; and 2) The effects of a characteristic change when all agents acquire more of it. Decision-makers seem to respond more to absolute than to relative differences among individuals. Weaker results show that an increase in the mean of a characteristic's distribution does not alter market responses to differences in it.
Keywords: J71; J78; 330; Beauty; Height; Discrimination; Market responses; Diskriminierung; Biologische Daten; Arbeitsmarktdiskriminierung; Schätzung; USA; Niederlande